10-hydroxy-2-decenoic acid alleviates lipopolysaccharide-induced intestinal mucosal injury through anti-inflammatory, antioxidant, and gut microbiota modulation activities in chickens - Han, Lianquan; Zhang, Maolu; Li, Fuwei; Su, Jing; Wang, Ruiming; Li, Guiming; Yang, Xiaohui (Frontiers in Microbiology, 2023)
Introduction This study aimed to investigated the effects of 10-hydroxy-2-decenoic acid (10-HDA) on the growth performance, intestinal barrier, inflammatory response, oxidative stress, and gut microbiota of chickens challenged with lipopolysaccharide (LPS). Methods A total of 240 one-day-old chickens were randomly assigned to five treatment groups: (1) control group (basal diet + saline); (2) LPS group (basal diet + LPS); (3) Chlortetracycline (CTC) group (basal diet containing 75 mg/kg CTC + LPS); (4) 0.1% 10-HDA group (basal diet containing 1 g/kg 10-HDA + LPS); and (5) 0.5% 10-HDA group (basal diet containing 5 g/kg 10-HDA + LPS). All chickens were injected intraperitoneally with 0.5 mg/kg body weight of either LPS or saline at 17, 19, and 21 days of age. Results The results showed that dietary 10-HDA supplementation attenuated the loss in growth performance caused by the LPS challenge (p < 0.05). 10-HDA effectively alleviated LPS-induced intestinal mucosal injury, as evidenced by reduced bleeding, decreased serum diamine oxidase levels (p < 0.05), and increased villus/crypt ratios of the jejunum and ileum (p < 0.05). Dietary treatment with 0.1% 10-HDA reduced the concentrations of inflammatory cytokines (TNF-α, IL-1β, IL-6; p < 0.05), and increased immunoglobulin (IgA, IgG) and antioxidant enzyme levels (CAT, GSH-px, T-SOD) in the serum of LPS-challenged chickens (p < 0.05). These effects were similar to those observed in the CTC group. Moreover, 0.1% 10-HDA treatment reversed the LPS-induced variations in the mRNA expression of genes related to inflammation, antioxidant capacity, and intestinal tight junctions (p < 0.05). 16S rRNA analysis revealed that 10-HDA supplementation increased the relative abundance of Faecalibacterium and Clostridia_UCG-014 (p < 0.05). Additionally, it decreased the abundance of Clostridia_vadinBB60_group, Eubacterium_nodatum_group, and UC5-1-2E3 (p < 0.05). These changes were correlated with reduced inflammation and improved antioxidant capacity in the LPS-challenged chickens. Conclusion Collectively, dietary 10-HDA supplementation alleviated LPS-induced intestinal mucosal injury and the loss of growth performance through anti-inflammatory, antioxidant, and gut microbiota modulation activities in chickens. Moreover, 0.1% 10-HDA supplementation had comparable or even better protection for LPS-challenged chickens than supplementation with antibiotics or 0.5% 10-HDA. 10-HDA has the potential to be used as an alternative to antibiotics in protecting the intestinal health and improving the performance of poultry.